Translating tools and indicators in territorial RRI - Völker, Thomas; Mazzonetto, Marzia; Slaattelid, Rasmus; Strand, Roger (Frontiers in Research Metrics and Analytics, 2023)
Introduction By a series of calls within the Horizon 2020 framework programme, the EU funded projects intended to deploy Responsible Research and Innovation (RRI) at a territorial level, in regional research and innovation ecosystems. This paper presents efforts to document and evaluate the achievements in TRANSFORM, one of these projects. Methods Evaluative inquiry and theoretical reasoning. Results Noting the need for a general principle to be interpreted, adapted and translated in order to be rendered meaningful at a local level, we studied precisely these multiple territorial translations of RRI, the organizational and institutional orderings with which they co-emerge and the challenges that come with these translations. An important shared feature is that RRI work does not start from zero, but rather builds on pre-existing relationships and repertoires of collaboration. The RRI project is hence a way to continue ongoing work and follow pre-set purposes, aims and objectives, as a form of “maintenance work”. In this very human sense, RRI is deployed with a logic of care in the regional context, while the Horizon 2020 calls and proposals above all are formulated in a logic of choice, to be assessed by indicators. Discussion We warn against undue standardization of RRI by toolification and use of quantitative indicators, and recommend that RRI performance is monitored by methods of evaluative inquiry.